THROMBOPHILIA AS A FACTOR OF ETHIOLOGY AND PATHOGENESYS OF DISORDERS IN THE SYSTEM “WOMAN – FETUS – NEWBORN” - A. Ya. Il'ina; P. V. Shumilov; A. L. Mishchenko; A. S. Barinova; I. Yu. Kokaya; V. N. Kashin; O. S. Pobedinskaya; I. V. Solov'eva; T. S. Kharlamova; A. V. Budancev; E. A. Akhalova (Акушерство, гинекология и репродукция, 2017)
Objective: the assessment of a condition of health of women with antiphospholipid syndrome (APS) and hereditary thrombophilia (HT) and a condition of health their newborn children.Materials and Methods. We examine clinically and by laboratorial and special exams (coagulogram, polymerase chain reaction diagnostics of genetics of hemostasis, ultrasonography of fetus at I, II, III trimester of pregnancy, doppler ultrasonography of blood flow in umbilical arteries, cardiotocography) 92 women with thrombophilia and their 92 newborn children (neurosonography, fundoscopy, abdominal ultrasound, nephrosonography, ultrasonography of hip joint).Results. The somatic anamnesis was more often burdened by vegetative dystonia syndrome (82.61%) at women with APS and by prolapse of the mitral valve (30.43%) and myopia (28.26%) at women with HT. In high percentage of cases fetoplacental insufficiency (60.78% at women with APS and 67.39% at women with HT), threatened miscarriage (50,00% at women with APS and 65.22% at women with HT) and cervical erosion (23.91% at women with APS and 45,65% at women with HT) was peculiarity of obstetric and gynecology anamnesis at all women with thrombophilia. Hypoxic-ischemic encephalopathy (78.26%), conjugation jaundice (56.52%) and morphofunctional dismaturity (45.65%) was diagnosed more often at children who was born to the women with APS and hypoxic-ischemic encephalopathy (65.96%) and intrauterine growth restriction (34.04%) was diagnosed at children who was born to the women with HT.Conclusion. Rather high percentage of diseases at women with thrombophilia and at their newborn children claim further development the therapy algorithm in the system “woman – fetus – newborn” with the case of decrease of the morbidity and improvement of social adaptation of newborn children in the future.